Cardiovascular and behavioral risk factors in relation to self-assessed health status - Vuletić Mavrinac, Gorka (Array, 2009)
The purpose of this study was to explore biomedical and behavioral risk factors in relation to self-assessed physical, mental and general health status in an open adult Croatian population sample. Subjective experience of health status was assessed with the Short Form 36 Health Survey questionnaire (SF-36). Out of 9070 respondents, we defined two groups with respect to cardiovascular (CV) risk factors: (1) a healthy group of individuals who did not state the presence of any covered chronic disease or disorder (N=1, 817), and (2) a group with CV risk which included individuals who reported having high blood pressure or high blood cholesterol or high blood sugar diagnosed (N=360). When adjusted for socio-demographic characteristics, these two groups differed in self-assessed health status. The group with CV risk factors showed an average lower level of subjective health status than the healthy group. At the level of specific health dimensions, the group with CV risks reported significantly lower general and mental health, but they reported healthier behaviors at the present time. We analyzed the measured health behaviors in predicting individual differences in the physical, mental and general health of the healthy group. Physical activity was revealed as a significant predictor of all three aspects of subjective health. Socio-economic variables of age, gender and self-assessed economic status contributed significantly to the explanation of all three aspects of subjective health. Our findings emphasize that psychological, physical, and social factors are inextricably linked in maintaining cardiovascular health, thus showing the importance of targeting health-related behaviors, especially physical activity, in preventive strategies and programs.